Nos fragmentos do Satíricon: a expressão da violência e vida entre rastros e relatos - Santos, Vinícius Medeiros [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
O objetivo deste trabalho é realizar um estudo sobre o romance antigo romano, especificamente sobre o Satíricon, de Petrônio, tendo como tema a manifestação da violência, fenômeno que integra expressões e procedimentos humanos em todos os tempos. Buscaremos promover uma reflexão acerca desse córpus, considerando o momento histórico de sua produção, a especificidade de sua elaboração textual (tais como estrutura narrativa, fragmentação e lacunas, imprecisões sobre o título, a autoria e a sua originalidade e a complexidade de sua mensagem), e sua inserção genérica como romance antigo, considerando as vertentes gregas e romanas. Ademais, avançando nos estudos sobre a expressão da violência especificamente aplicada e manifesta nesse romance elencado de modo a contribuir para com sua fortuna crítica, analisaremos a manifestação do fenômeno da violência nessa narrativa, cujo protagonista não só tem uma trajetória de início fomentada por um evento violento de natureza bem específica, qual seja, a sexual, mas também,

The main purpose of this investigation is to carry out a study about the ancient Roman novel, specifically related to Petronius' Satyrica, considering the theme of violence’s manifestation, a phenomenon which integrates human expressions and procedures throughout history. We intend to promote a critical thinking regarding this novel, considering the historical moment of its production, the specificity of its textual elaboration (such as narrative structure, fragmentation and textual gaps, inaccuracies related to the title, authorship and its originality, and finally the complexity of its message), besides its generic insertion as an ancient novel, considering the Greek and Roman aspects. Furthermore, in order to move towards to a possible clarifications about studies of violence's expressions specifically applied and manifested in this novel, we are going to analyze the manifestation of the phenomenon of violence in this narrative, whose protagonist not only has a journey set off by an violent event of a very specific nature, meaning a sexual action, but also, throughout the plot, his trajectory is marked by many other violent aspects. To do so, and even though violence can be understood as a transgressive force, we point out to the fact that the violence’s expression can prove to be productive and promote life. Thus, even if our assumptions at first sight seem to be contradictory, in our investigations, for example, we reflect on how the violence instigated against sex [Priapus' phallus] promotes both the emergence of life itself and its subsequent reorganization, now, in other words, a new beggining.
Throughout Satyrica's fragments: the expression of life and violence between traces and stories
Keywords: Violência; Romance antigo romano; Petrônio; Violence; Ancient Roman novel; Petronius